До питання компонування спеціалізованих ширококолійних енерготехнологічних транспортних засобів для колійної системи землеробства - Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; Kuvachov, Volodymyr (КНТУ, 2016)
UK: В статті розглядаються питання оптимального компонування спеціалізованих ширококолійних енерготехнологічних транспортних засобів для колійної системи землеробства з позиції їх задовільної стійкості та плавності руху. RU: В статье рассматриваются вопросы оптимального компонирования специализированных ширококолейных энерготехнологических транспортных средств для колейной системы земледелия с позиции их приемлемой устойчивости и плавности хода. EN: The purpose of this research is to increase the efficiency of the operation and use of wide span vehicles for the controlled traffic farming by selecting an optimal design scheme from the position of reasonable stability and smoothness. Based on the theory of plane-parallel movement of the wide span vehicles in vertical and horizontal planes the impact of its technological part on the amplitude-frequency characteristics testing dynamic traction system is estimated. In the variant the central mounting of agricultural implements, in contrast to the rear, improves the stability of the wide span vehicles, but significantly deteriorating the dynamics of its vertical oscillations is established.
К вопросу компоновки специализированных ширококолейных энерготехнологических транспортных средств для колейной системы земледелия
To the question of design the wide span vehicles for controlled traffic farming
Keywords: мостове землеробство; колійне землеробство; стійкість руху; плавність руху; компонування; амплітудно-частотні характеристики; ширококолейное агросредство; мостовой трактор; устойчивость хода; плавность хода; компоновка; амплитудно-частотные характеристики; wide span vehicles; controlled traffic farming; stability; smoothness; agriculture; theoretical studies; amplitude-frequency characteristics